A ética empresarial como instrumento de efetivação dos direitos sociais: o desafio diante à atuação das empresas transnacionais no mercado globalizado - Bonotti, Rachel Vecchi (2022)
Economic activities have always been present in society, and in each historical period, it has been carried out in a certain way. As cities evolved, mainly in the face of scientific and technological progress, it brought changes in the perspectives of market performance, and, after the Second World War, these companies began to act on a global scale, with the exchange of products, services and technology, which travel all over the planet. The transnational companies, responsible for these activities, rescue liberal conceptions for the non-intervention of the State, to freely exercise their activity, resulting, therefore, in a repeated way, in violations of human rights. Faced with the new reality of the contemporary world, transactions and markets on a globalized scale, a new business posture is necessary, and in this way, it is assumed that business ethics presents itself as an effective instrument for promoting and respecting human rights. social, since ethics orders criteria and imposes behaviors in these business activities, in all aspects. In view of this, the present dissertation aims at the historical analysis of human rights, the changes that have taken place in mercantile activities, and how currently, in the face of globalization and the performance of transnational companies in the world, there are still several violations of human rights, and how business ethics can interfere and modify these issues, under the ideals of human development together with the economic progress of society. The work has an exploratory character and seeks to investigate, through bibliographic review and academic research, the main concepts related to the theme, and, using the deductive method, responds to this problem, presenting as a result that business ethics in the face of the performance of transnational companies in the globalized market, presents itself as an instrument for the realization of social rights. It is concluded, then, that business ethics, through business policies, meets the aspirations of the new globalized market within the capitalist system for economic development, but also in line with the scope of human development in relation to social rights, being, finally, an instrument for the realization of human rights.